Factors Affecting Sorghum Production in Western Ethiopia: Evidence from Smallholder Farmers - Kifle Degefa; Galmesa Abebe; Getachew Biru (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Sorghum is the most important cereal crop in Sub-Saharan Africa including Ethiopia. The productivity and production of the crop are not increased as expected due to many limitations in the generation of demand-driven technologies and innovation upscaling in integrated and impact-oriented approaches to sorghum production. The study was focused on sorghum production systems and factors affecting sorghum production for sorghum producers. For this study both purposive and random sampling techniques were applied to select 123 households. OLS regression was used to analyze factors affecting sorghum productivities. In the study areas, the majority of the farmers used the local sorghum variety. Only 17.89% of sample households used improved sorghum varieties including lalo, chemeda, and gemedi varieties. The technology attributes improved sorghum varieties were better performance than the local variety. The regression model revealed that variables including sex, age, education, improved variety, soil slope and fertility, TLU, and extension services affected sorghum productivity positively and significantly at 10%, 5%, and 1% significance levels. Respective experts (BoANR, research centers, NGOs, and Universities) should be advised and support sorghum producers to enhance sorghum productivity.